A hypoplastic constitutive model for structured soils. (November 2022) - He, Yu-Qi; Wang, Shun; Liao, Hong-Jian; Wu, Wei
Abstract: Natural soils usually exhibit microstructure effects that significantly influence their engineering properties; however, existing hypoplastic constitutive models rarely consider structural evolution during loading. This paper presents a hypoplastic constitutive model for structured soils. A structural factor that combines the initial structure degree and the overconsolidation ratio is introduced to describe the structure effects induced by the soil deposition and stress histories, respectively. A structure degradation law is adopted to capture the destructuring process during loading. Thus, this model can describe the mechanical behaviours of both structured and reconstituted soils with normal consolidation and over-consolidation at various stress levels. The model is further verified by comparing numerical predictions with experimental data. The comparison suggests that the proposed model can reproduce the salient behaviours of structured soils under various testing conditions.